ANALISIS PERBANDINGAN KOIL PENGAPIAN STANDARD DAN KOIL PENGAPIAN AFTERMARKET TERHADAP KINERJA SEPEDA MOTOR 4 LANGKAH - Sugeng, Margono; Mukti, yasin (Bina Teknika, 2019)
ABSTRACTThis study aims to determine the engine performance (torque, power, and air fuel ratio / AFR) with a variation of the Standard and aftermarket Ignition Coil on the Honda Astrea Legenda 100cc motorbike. The research method used is the experimental method and carried out at the rotating speed (rpm) change, namely by turning on the engine and opening the gas 3000 rpm to full throttle. From testing the engine performance, it can be concluded that the greatest power is obtained by using the Aftermarket SGP RM 80 Ignition Coil with a power of a maximum of 6.83 hp at 6100 rpm engine speed. The biggest torque was also obtained by the Aftermarket SGP Ignition Coil RM 80 of 5.89 ft-lbs at 6100 rpm engine speed. From AFR testing, it can be concluded that the level of air and fuel ratio (AFR) produced by the aftermarket ignition coil is more fuel efficient based on the Stoichiometric graph. Using this aftermarket ignition coil starts from the AFR 17.66: 1 to 14.50: 1. Keywords: Motorcycle, ignition coil, Power, Torque, AFR